Organizational innovation and creativity perception of public sports organization employees in Turkey - Nuh Osman Yildiz (ROL Spor Bilimleri Dergisi)
Globalization in today's business world brings different problems for every sector and every institution. The solution to these problems will only be possible by offering innovative and creative solutions. Self-development of innovative individuals will also take place through the support provided by their organizations. This situation makes it important to investigate whether there is an innovative and creative working climate provided by the organization in terms of innovation and creativity of the employees. This is also true for the employees of the Ministry of Youth and Sports of Turkey, which is the public institution and organization that directs the sports sector, which is one of the world's major economies, on a country basis. In this context, this study aims to examine the innovation and creativity perceptions of the employees of the central and provincial organizations of the Ministry of Youth and Sports. The study was designed according to the correlational survey model and causal-comparative research in quantitative research methods. The study group was determined according to the convenience sampling method, which is one of the non-random sampling methods. The working group comprised of 424 Ministry of Youth and Sports central and provincial employees. In the study, the “Innovation Climate Scale” was used as a data collection tool. In the analysis of the obtained data, parametric tests were used after the normality examination. As a result of the analyzes, it was determined that the innovativeness perceptions of the employees of the central and provincial organizations of the Ministry of Youth and Sports are above the average. In conclusion, it can be stated that the employees of the central and provincial organizations of the Ministry of Youth and Sports of Turkey work in an innovative and creative organizational environment.